Methanogenesis produces strong 13C enrichment in stromatolites of Lagoa Salgada, Brazil: a modern analogue for Palaeo‐/Neoproterozoic stromatolites?. Issue 3 (13th March 2015) - Birgel, D.; Meister, P.; Lundberg, R.; Horath, T. D.; Bontognali, T. R. R.; Bahniuk, A. M.; de Rezende, C. E.; Vasconcelos, C.; McKenzie, J. A.
Abstract Holocene stromatolites characterized by unusually positive inorganic δ13CPDB values (i.e. up to +16‰) are present in Lagoa Salgada, a seasonally brackish to hypersaline lagoon near Rio de Janeiro (Brazil). Such positive values cannot be explained by phototrophic fixation of CO2 alone, and they suggest that methanogenesis was a dominating process during the growth of the stromatolites. Indeed, up to 5 mm methane was measured in the porewater. The archaeal membrane lipid archaeol showing δ13C values between −15 and 0‰ suggests that archaea are present and producing methane in the modern lagoon sediment. Moreover, 13C‐depleted hopanoids diplopterol and 3β‐methylated C32 17β(H), 21β(H)‐hopanoic acid (both −40‰) are preserved in lagoon sediments and are most likely derived from aerobic methanotrophic bacteria thriving in the methane‐enriched water column. Loss of isotopically light methane through the water column would explain the residual 13C‐enriched pool of dissolved inorganic carbon from where the carbonate constituting the stromatolites precipitated. The predominance of methanogenic archaea in the lagoon is most likely a result of sulphate limitation, suppressing the activity of sulphate‐reducing bacteria under brackish conditions in a seasonally humid tropical environment. Indeed, sulphate‐reduction activity is very low in the modern sediments. In absence of an efficient carbonate‐inducing metabolic process, we propose that stromatolite formation in Lagoa Salgada was abiotically induced, while the 13C‐enriched organic and inorganic carbon pools are due to methanogenesis. Unusually, 13C‐enriched stromatolitic deposits also appear in the geological record of prolonged periods in the Palaeo‐ and Neoproterozoic. Lagoa Salgada represents a possible modern analogue to conditions that may have been widespread in the Proterozoic, at times when low sulphate concentrations in sea water allowed methanogens to prevail over sulphate‐reducing bacteria.